O desenvolvimento da disciplina da transação no direito privado brasileiro e seu papel como instrumento de autoregulação dos conflitos entre particulares - Siebeneichler De Andrade, Fábio (Pontificia Universidad Católica del Perú, 2023)
The work intends to examine the particularities of the settlement as a contract, based on the recognition of this legal nature, by the Civil Code of 2002. Since settlement is a legal instrument of great practical and theoretical importance, whose main purpose lies in serving to regulate conflicts between individuals, through reciprocal concessions, it is considered necessary to highlight and examine its particularities, within the framework of contracts and verify the development given to it by jurisprudence in the twenty years of validity of the 2002 Civil Code. Furthermore, it is worth highlighting the new position attributed to settlement by the new Brazilian Civil Procedure Code of 2015.

O trabalho pretende examinar as particularidades da transação como contrato, a partir do reconhecimento dessa natureza jurídica, pelo Código civil de 2002. Sendo a transação instrumento jurídico de grande importância prática e teórica, cuja finalidade precípua reside em servir para a regulação de conflitos entre particulares, mediante as concessões recíprocas, reputa-se necessário destacar e examinar suas particularidades, no quadro dos contratos e verificar o desenvolvimento dado a ela pela jurisprudência nos vinte anos de vigência do Código civil de 2002. Além disso, cumpre destacar a nova posição atribuída à transação pelo novo Código de Processo Civil brasileiro, de 2015.
The development of the discipline of settlement in brazilian private law and its role as an instrument for self-regulation of conflicts between private parties
Keywords: Settelment agreement; Selfregulation of conflicts; Civil Code; Comparative Law; Civil Law; Brazil; Transação; Autoregulação de conflitos; Código Civil; Direito Comparado; Direito Civil; Brasil; https://purl.org/pe-repo/ocde/ford#5.05.00